2014
DOI: 10.4103/2277-9175.125812
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status in patients with ulcerative colitis in Isfahan, Iran

Abstract: Background:Malnutrition is common among patients with inflammatory bowel disease. The present study aimed to investigate the nutritional status of ulcerative colitis (UC) patients in Isfahan, Iran.Materials and Methods:In this descriptive analytical cross-sectional study, between Dec 2011 and Jun 2012, 99 patients with UC were randomly selected and evaluated. Age, sex, duration of disease, body mass index (BMI) and laboratory parameters recorded for all patients. Nutritional risk index (NRI) was calculated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In this study, vitamin D was deficient in 73.8% of patients with IBD being the second most frequent micronutrient deficiency after iron deficiency. Kalantari et al [ 2 ] also reported a higher prevalence of vitamin D deficiency in their pediatric patients with UC (87%). Nonetheless, this prevalence is still considered low compared to that of healthy age-matched counterpart children in Bahrain where vitamin D deficiency prevalence is extremely high (93.4%) [ 45 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, vitamin D was deficient in 73.8% of patients with IBD being the second most frequent micronutrient deficiency after iron deficiency. Kalantari et al [ 2 ] also reported a higher prevalence of vitamin D deficiency in their pediatric patients with UC (87%). Nonetheless, this prevalence is still considered low compared to that of healthy age-matched counterpart children in Bahrain where vitamin D deficiency prevalence is extremely high (93.4%) [ 45 ].…”
Section: Discussionmentioning
confidence: 98%
“…Motil et al [ 40 ] study showed no significant difference in vitamin B12 levels between children with CD and those with UC. Yet, Kalantari et al [ 2 ] reported a remarkably high proportion of vitamin B12 deficiency in adult patients with mild and moderate to severe UC (35% and 50%, respectively). Fritz et al stated that screening for vitamin B12 deficiency should be limited to patients with ileal or ileocolonic resection, and those with suspected malabsorption [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition is present in the vast majority of patients with inflammatory bowel disease (IBD), the deficiencies being more prevalent in Crohn’s disease compared with ulcerative colitis and more important in active diseases [68]. Micronutrient deficiencies are essentially explained by the reduced dietary intake and the underlying malabsorption.…”
Section: Disease Specific Deficiencymentioning
confidence: 99%
“…On the other hand, inadequate nutritional support in these patients can result in deterioration of nutritional status and progress of malnutrition during hospitalization. [ 15 16 17 ] In summary, nutritional status monitoring and optimal nutritional delivery are essential practice in the critically ill patients which can reduce morbidity, mortality, and hospitalization costs. [ 18 19 ]…”
Section: Introductionmentioning
confidence: 99%